An Annealing Memetic Algorithm for Instructional Scheduling - Shen-min Lv (International Journal of Emerging Technologies in Learning (iJET), 2018)
In order to solve the problems of large-scale instructional scheduling, many constraints, and complex interrelation, it is studied based on the changes in the scheduling problem and the adjustment of related algorithms. Firstly, the problem of instructional scheduling is described as a whole, and the relationship between each stage, in particular the impact of the combined plan on scheduling is also described, and an optimization plan is proposed. Then the optimal scheduling scheme is solved with Memetic algorithm. According to the constraints, the fitness value function in the algorithm is designed flexibly. Finally, the convergence of the algorithm is proved based on the Banach compression mapping theorem. Practice has proved that: Memetic algorithm can effectively solve the problem of inadequate teaching resources and difficult of instructional scheduling. Therefore, the Memntic algorithm can be used in instructional scheduling.